1992
DOI: 10.1007/bf02341917
|View full text |Cite
|
Sign up to set email alerts
|

The role of co-skewness in the pricing of real estate

Abstract: The current study investigates whether systematic skewness offers an alternative perspective as to why the riskadjusted returns on real estate should be similar to that for stocks. This is not a trivial issue since an affirmative finding implies that we might be incorrectly measuring real estate risk from both a pricing and a portfolio allocation perspective. A multivariate test of the Kraus-Litzenberger model is used to investigate this skewness proposition with the K-L CAPM tested against several alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…Vines et al (1994) investigated the role of co-skewness in the pricing of equity REITs. Contrary to Liu et al (1992), their study found no evidence that co-skewness is a determinant of REIT returns.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Vines et al (1994) investigated the role of co-skewness in the pricing of equity REITs. Contrary to Liu et al (1992), their study found no evidence that co-skewness is a determinant of REIT returns.…”
Section: Introductionmentioning
confidence: 74%
“…Liu et al (1992) use CREF data to examine the impact of co-skewness on real estate returns and found evidence that co-skewness does provide some explanatory power to real estate returns. Vines et al (1994) investigated the role of co-skewness in the pricing of equity REITs.…”
Section: Introductionmentioning
confidence: 99%
“…This renders application of theories like the mean-variance portfolio optimization to real world data problematic and further fuels the concerns discussed above. Among others, Liu et al (1992) and Myer and Webb (1993) first provided evidence for this. Using non-normality in their MPT application, Byrne and Lee (1997) show that the National Council of Real Estate Fiduciaries (NCREIF) data is non-normal.…”
Section: Introductionmentioning
confidence: 92%
“…Liu, Hartzell and Grissom (1992) are the first to test whether systematic skewness is priced in real estate returns. They employ quarterly appraisal-based data on five commingled real estate funds (CREFs) from 1979 to 1989 for a multivariate test of the Kraus-Litzenberger model.…”
Section: Higher Moments In Real Estate Returnsmentioning
confidence: 99%